Formulation and evaluation of nanobiotherapeutics of Terminalia arjuna through plant tissue culture for atherosclerosis - Pradnya Pradeep Wadekar; Vijay Rajaram Salunkhe (SpringerOpen, 2024)
Abstract Background The study seeks to investigate the therapeutic potential of Terminalia arjuna callus in addressing atherosclerosis. In order to get maximum beneficial phytoconstituents from Terminalia arjuna, it is recommended to harvest the bark from Arjuna trees that are at least 15 years old and a gap of minimum 2 years should be kept before harvesting bark from the same plant. The callus culture technique was employed to expedite the process. The callus culture extract was subsequently converted into a nanosuspension with the aim of improving the efficacy of its phytoconstituents. It was then subjected to a comprehensive series of in vitro and in vivo evaluations to ascertain its potential for treatment of atherosclerosis. Results Liquid chromatography-mass spectrometry analysis of the callus extract confirmed the presence of flavonoids and terpenoids, known for their antioxidant and anti-inflammatory activities. Some terpenoids were even absent in Arjuna tree naturally. TEM images validated successful entrapment of the extract within the nanoparticles. In vitro analysis for antilipase and antioxidant assay confirmed the antiatherosclerotic potential of the extract. In vivo tests on rat blood serum demonstrated a significant reduction in total cholesterol, low-density lipoprotein, triglycerides, high-density lipoprotein, and very low-density lipoprotein. Histopathological analysis of rat aortas showed additional confirmation of antiatherosclerotic action. Conclusion In conclusion, the study highlights the potential of nanosuspension derived from Terminalia arjuna callus extract as a comprehensive therapeutic strategy for atherosclerosis treatment. The research highlights antioxidant, anti-inflammatory, and antiatherosclerotic properties of the callus, hinting at its viability as a potential treatment for atherosclerosis. This interdisciplinary investigation emphasizes the promising role of traditional medicinal plants within modern medical paradigms.